2021
DOI: 10.21511/ppm.19(4).2021.04
|View full text |Cite
|
Sign up to set email alerts
|

Technological perspectives of a balanced scorecard for business incubators: Evidence from South Africa

Abstract: This study was deemed relevant in the current epoch given the need for rebuilding enterprises that were devastated by the Covid-19 pandemic. To ensure economic restoration, particular interest in small business start-ups and incubators has become especially important. In addition, measurements for effectiveness are critical since, without them, progress cannot be ascertained. The aim of this study was to assess the balanced scorecard and its applicability to business incubators in the context of the present te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The study also analysed the most productive authors with regards to business incubation in South Africa. Figure 2 shows that Lose stands out as the prominent author with seven publications (Lose & Khuzwayo, 2021;Lose, 2021;Lose & Kapondoro, 2020;Lose, Yakobi & Kwahene, 2020;Lose, Tengeh, Maziriri, & Madinga, 2016;, followed by Rogerson (Rogerson, 2017;Masutha & Rogerson, 2015;Masutha & Rogerson, 2014a;Masutha & Rogerson, 2014b) and Tengeh (Lose, Tengeh, Maziriri, & Madinga, 2016;Lose & Tengeh, 2015) who have 4 publications each, Masutha (Masutha & Rogerson, 2015;Masutha & Rogerson, 2014a;Masutha & Rogerson, 2014b), and Strydom (Strydom, Kempen & Tselepis, 2023;Strydom, Kempen & Tselepis, 2021;Strydom, 2021) have 3 publications each, Iwu (Dlamini, Iwu, & Ogunlela, 2023;Eresia-Eke, Iwu, Jaiyeola & Musikavanhu, 2019) and Schmitt (Schmitt, 2023;Schmitt, 2022) with 2 publications each and the rest of the authors as shown have one publication each. The dataset of 254 keywords was limited to a minimum number of three occurrences, whereas 31 items met the threshold.…”
Section: Documents By Authormentioning
confidence: 99%
“…The study also analysed the most productive authors with regards to business incubation in South Africa. Figure 2 shows that Lose stands out as the prominent author with seven publications (Lose & Khuzwayo, 2021;Lose, 2021;Lose & Kapondoro, 2020;Lose, Yakobi & Kwahene, 2020;Lose, Tengeh, Maziriri, & Madinga, 2016;, followed by Rogerson (Rogerson, 2017;Masutha & Rogerson, 2015;Masutha & Rogerson, 2014a;Masutha & Rogerson, 2014b) and Tengeh (Lose, Tengeh, Maziriri, & Madinga, 2016;Lose & Tengeh, 2015) who have 4 publications each, Masutha (Masutha & Rogerson, 2015;Masutha & Rogerson, 2014a;Masutha & Rogerson, 2014b), and Strydom (Strydom, Kempen & Tselepis, 2023;Strydom, Kempen & Tselepis, 2021;Strydom, 2021) have 3 publications each, Iwu (Dlamini, Iwu, & Ogunlela, 2023;Eresia-Eke, Iwu, Jaiyeola & Musikavanhu, 2019) and Schmitt (Schmitt, 2023;Schmitt, 2022) with 2 publications each and the rest of the authors as shown have one publication each. The dataset of 254 keywords was limited to a minimum number of three occurrences, whereas 31 items met the threshold.…”
Section: Documents By Authormentioning
confidence: 99%
“…In which this performancemeasuring tool covers every aspect that then grouped into four main perspectives, namely: financial perspective, growth and learning perspective, internal business process perspective, and customer perspective. (Zeho, Setyowati, Hermawan, 2020;Lueg & Julner, 2014) According Lose & Khuzwayo (2021) the Covid-19 virus has threatened to exacerbate in many developing counties developmental issues, so it is essential to sort out how to re-enforce small company incubation. According to Guillen (2020), the virus is a problem that needs both immediate and longterm solutions.…”
Section: Strength Of Balance Scorecardmentioning
confidence: 99%
“…Bruneel et al (2012) have categorised the models into three generations, with increasing offerings in each subsequent generation. South Africa currently has a mix of all three generations, with some business incubators failing to meet best practice standards (Lose & Khuzwayo 2021;Meyer & Meyer 2016). The critical skills South African entrepreneurs need include financial management, human resource management, Start-up, social and interpersonal, business leadership, business personality, marketing, technical, and business management (Mamabolo et al, 2017).…”
Section: Figure 1 Evolution Of Business Incubator (Bi) Modelsmentioning
confidence: 99%